Faktor Yang Mempengaruhi Serangan Jantung Berulang Pada Pasien AMI Di Ruang ICVCU RSUD Dr. Moewardi Tahun 2016 - Fransisca Saktiningtyastuti; Sri Lestari Dwi Astuti ((JKG) Jurnal Keperawatan Global, 2017)
Abstract: Consumed Cholesterol Foods, Hypertension, Smoked, Diabetes Mellitus, Exercise, Sleep Quality, Recurrent Heart Attack. Smoking, consuming cholesterol foods, and staying up all night are easy to find in around us. Moreover, some of people that have historic of heart disease, hypertension, or diabetes mellitus haven’t pay attention with their lifestyle. Eventhough, consumed cholesterol foods, hypertension, smoked, diabetes mellitus, exercise and sleep quality are can affected recurrent heart attack of patients with acute myocardial infarction in ICVCU Dr.Moewardi hospital in Surakarta. Design of this research is a descriptive analytic with cross sectional approach. The sampling method is total sampling. Analysis of data used chi square, fisher and regression logistic. The result of research obtained factors that affected recurrent heart attack of patients with acute myocardial infarction is consumed cholesterol foods (p=0,039), hypertension (p=0,014), smoked (p=0,038), diabetes mellitus (p= 0,014), exercise (p= 0,014), and sleep quality (p= 0,014). Hypertension and exercise are the greatest influence (OR= 0,065), next consumed cholesterol foods (OR= 0,052), and diabetes mellitus (OR= 0,035). Conclusion: Dominant factors that affected recurrent heart attack of patients with acuce myocardial infarction are hypertension and exercise.